Integrated National Policy Approaches to Climate-Smart Agriculture. Insights from Brazil, Ethiopia, and New Zealand - Negra, Christine (2014)
In the absence of clear international policy signals and strong global agreements on climate change and sustainable agriculture, countries are moving forward to test sustainability strategies through innovative policies and financing programmes. This paper explores how three countries – Brazil, Ethiopia, and New Zealand – are using integrated policy approaches to address the linked challenges of climate change, unsustainable agriculture, and food insecurity. To explore the major technical and institutional components that are fundamental to national climate-smart agriculture (CSA) policy, each of these three countries are reviewed for their role in the global food and climate systems, their major national climate and agriculture policies, and their investments in capacity building and policy innovation.